1994
DOI: 10.1002/ana.410360516
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular human T‐cell lymphotropic virus type I tax protein induces cytokine production in adult human microglial cells

Abstract: Tropical spastic paraparesis (HAM/TSP) is caused by human T-cell lymphotropic virus type I (HTLV-I) infection. Although the virus infects T cells in vivo and is capable of infecting microglia in vitro, the inflammatory demyelination has not been linked to virus in central nervous system tissue. Thus, indirect mechanisms (e.g., cytokines) could be involved in demyelination and inflammation. The ability of HTLV-I Tax protein to induce tumor necrosis factor-alpha (TNF-alpha), interleukin-1 beta (IL-1 beta), and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 12 publications
2
50
0
1
Order By: Relevance
“…Indeed, accumulating evidence suggests that extracellular Tax can act by binding to an unknown cell surface receptor(s) on target cells, and induce expression of a number of proin¯ammatory cytokines. Extracellular Tax has been shown to induce the production of interleukin-1b (IL-1b), IL-6, tumor necrosis factor-a (TNF-a) in macrophages, and microglial cells in a dose-dependent manner (Dhib-Jalbut et al, 1994). Additional studies will be required to determine the mechanism of extracellular Tax-mediated cytokine expression.…”
Section: Viral Mechanisms Regulating Htlv-i Infection In Target Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, accumulating evidence suggests that extracellular Tax can act by binding to an unknown cell surface receptor(s) on target cells, and induce expression of a number of proin¯ammatory cytokines. Extracellular Tax has been shown to induce the production of interleukin-1b (IL-1b), IL-6, tumor necrosis factor-a (TNF-a) in macrophages, and microglial cells in a dose-dependent manner (Dhib-Jalbut et al, 1994). Additional studies will be required to determine the mechanism of extracellular Tax-mediated cytokine expression.…”
Section: Viral Mechanisms Regulating Htlv-i Infection In Target Cellsmentioning
confidence: 99%
“…Recent studies have shown that Tax may be released from an infected cell and act as an extracellular cytokine on neighboring cells in the CNS. Extracellular Tax has been shown to induce NF-kB nuclear localization, and the expression of the immunoglobulin k light chain, IL-2Ra, IL-1b, IL-6, TNF-a, and TNF-b Lindholm et al, 1992;Marriott et al, 1992;Dhib-Jalbut et al, 1994). Possible mechanisms responsible for the cytokinelike effects of Tax may include extracellular Tax inducing a signaling cascade by binding to a speci®c cell surface receptor, or by the internalization and nuclear localization of extracellular Tax.…”
Section: Transition From Normal Immune Surveillance To Neuroinflammationmentioning
confidence: 99%
“…4). We found that Quin-IR in the controls also increased to some extent over (35)(36)(37). Quin has been reported to be increased in the CSF in response to other viral infections including HIV-1 and SIV (8)(9)(10); however, the cellular origin of Quin is unclear.…”
Section: Resultsmentioning
confidence: 71%
“…Based on biochemical studies, MOs have been hypothesized to be a potential source of Quin (11,38). In preliminary studies, we found that Quin-IR MOs/microglia were detectable in rat brain parenchyma after intracerebral injection of lipopolysaccharide (15) (37,41,42). IFN-y increased Quin-IR from -4% to 20%, but HTLV-I increased Quin-IR from -4% to 40%.…”
Section: Resultsmentioning
confidence: 99%
“…Prolonged treatment with Tax resulted in Tax-dependent cell death (300). Similarly, Dhib-Jalbut et al demonstrated that extracellular Tax also induced TNF-alpha and IL-6 expression in primary adult human microglia and peripheral blood macrophages (182). Therefore, circulating extracellular Tax in CNS, which either diffuses into the CNS from peripheral blood or secreted by CD4 + T cells, infiltrating the CNS can upregulate inflammatory cytokine expression resulting in neural degeneration in TSP patients in absence of detectable amount of the HTLV-I virus (269).…”
Section: Htlv-i and Tropical Spastic Paraparesis (Tsp)mentioning
confidence: 92%